Acceptance and feasibility for handheld Tele-ECG - Davalagi, Shubha; Palicheralu, Balu; Murthy, Sanjana; Kashyup, Manisha (Indian Journal of Community Health, 2020)
Background: In a developing country like India where mobile phone usage is increasing at an exponential rate, tele monitoring techniques could be used to reduce cardiac related morbidity and mortality. The current study was undertaken to evaluate the acceptance and feasibility of handheld tele-ECG for screening general population for cardiac related abnormalities. Methods: The study was conducted among walk-in patients and their attenders of an urban health training centre attached a tertiary care teaching hospital for a period of 6 months in 2019. Results: Among the 410 respondents, majority were of age group 30-39yrs (54%) and females (62%). Left ventricular hypertrophy (15.4%) was the commonest abnormality. Majority (97.5%) were very satisfied with the hand held Tele-ECG instrument. Conclusion: Telecardiology has a potential to revolutionize the healthcare system particularly in resource poor rural and urban slum settings in bridging the gap between primary and secondary care.